MINORITY MUSLIMS IN NORTH BALI: IDENTITY ON THE MAKING (Religion, Culture, and State Journal, 2022)
Indonesia faces specific problems in creating and maintaining national unity due to the heterogeneity of its citizens. Identification with and primary loyalty to the nation has to be reconciled with different regional groupings which draw on language, custom, and religion to preserve their distinctiveness. Many of these complex patterns of identity may be called ‘ethnic’ and have the potential to divide the nation internally. The investigation of socio-religious and cultural plurality in such an ethnically rich nation as Indonesia challenges us to identify not only the essential factors responsible for maintaining cultural group identity, but also to show how this occurs within the broader achievement of national unity. The purpose of my study of the Muslim Balinese community in Pegayaman is to clarify issues involved in cultural heterogeneity In this case the socio-cultural diversity of Indonesia is manifest in Bali more in religious rather than in broader ‘ethnic’ category.This article generally depicts the way the Muslims of Pegayaman in Northern Bali have maintained a separate socio-religious and cultural identity amidst a majority of Hindu-Balinese. Although their livelihood is heavily surrounded by an environment where the socio religious norms of the majority of population are different to their own, they have succeeded in maintaining their separate cultural identity. This study will pay specific attention to the following areas: 1) the Muslims defense mechanism vis-à-vis external challenges to their collective integrity; and 2) the degree to which the Muslims interact with the Hindu population.